Some caveats about the ‘Atlantic’ paradigm - Cañizares-Esguerra, Jorge (History compass, 2003)
Atlantic history is becoming increasingly fashionable. For colonial North American history in particular, this new perspective has proven genuinely liberating. It has allowed historians to escape the traditional teleological narratives of the nation. The colonial history of what would later be the United States has long been cast in rather narrow conceptual and geographical terms. Narratives exploring the vicissitudes and exploits of European settlers, as they allegedly went about creating the foundations of the new nation somewhere on the northeast coast, had crowded the field. This paradigm has come tumbling down as scholars now study developments in areas well beyond the British continental colonies. Historians currently maintain that the territories that came together to form the original union were part of a much larger Atlantic, namely, colonial British, French, Dutch, and Spanish worlds, each made up of a multitude of historical actors. This change of perspective, to be sure, is most welcome.